Alteration of the relative vibration of the round window membrane after implantation of a direct acoustic cochlear implant. (30th April 2020) - D'hondt, Christiane; Wouters, Jan; Verhaert, Nicolas
Abstract: Objective: Subjects implanted with a Direct Acoustic Cochlear Implant (DACI) show improvements in their bone conduction (BC) thresholds after surgery. We hypothesised that a new pathway for BC sound is created via the DACI. The aim of this study was to investigate the contribution of this pathway to the cochlear response via measurements of the promontory and round window membrane (RWM) velocities while stimulating with a conventional bone conductor. Design: This study was a cadaver head study with a repeated measures study design. Study Sample: Eight ears of five fresh-frozen cadaveric whole heads were investigated in this trial. Results: After DACI implantation the promontory and RWM velocities did not change significantly in the frequency range 0.5–2 kHz when the DACI was switched off. Conclusions: No significant changes in the relative vibration magnitude of the RWM after DACI implantation were observed. The improvements in BC thresholds seen in patients implanted with a DACI very likely have their origin in the changed impedance at the oval window after DACI surgery leading to a more efficient contribution from the inner ear components to BC sound.